Fedratinib for the treatment of myelofibrosis: a critical appraisal of clinical trial and “real-world” data - Adrian Duek; Ilona Leviatan; Osnat Jarchowsky Dolberg; Martin H. Ellis (Blood Cancer Journal)
Abstract Fedratinib is a predominantly JAK2 inhibitor that has shown efficacy in untreated and ruxolitinib-exposed patients with myelofibrosis (MF). Based on randomized clinical trial data, it is approved for use in patients with International Prognostic Scoring System (IPSS) or Dynamic International Prognostic Scoring System (DIPSS) intermediate-2 or high-risk disease and is distinguished from ruxolitinib in that it can be administered without dose reduction in patients with thrombocytopenia, to a platelet count above 50,000/µL. In these trials, fedratinib achieved significant spleen volume reduction in ~30–45% of patients and improvement in total symptom scores in 35–40% with good tolerability. In contrast, recently published real-world data suggest that these responses may not be as robust outside clinical trials. In the context of routine clinical practice spleen responses are documented in only 13–68%, with varying degrees of symptom improvement. This may be due to the lack of a uniform definition of ruxolitinib failure, which may influence the timing of initiating fedratinib as a second-line treatment and result in a more prolonged exposure to ruxolitinib prior to intitaing fedratinib treatment. We suggest that given the growing number of drugs available for use in MF, recognizing the failure of first-line (and potentially subsequent) treatments is critical to allow timely transition to potentially more active agents, as highlighted by the data pertaining to fedratinib.